Dynamic reallocation and rescheduling of steel products using agents with strategical anticipation and virtual marketstructures. Issue 20 (2016) - Neuer, Marcus J.; Marchiori, Francesca; Ebel, Alexander; Matskanis, Nikolaos; Piedimonti, Luca; Wolff, Andreas; Mathis, Gael
Abstract: A multi-agent system for the steel production is presented. It re-allocates off-spec products to existing alternative orders. The system consists of three main Industry 4.0 components: agents, service-oriented architecture (SOA) and a semantic modelling of the process chain. Using economic principles like virtual marketplaces, the solution of the reallocation is reached by means of auctions, where product agents act as sellers and order agents act as bidders. A virtual price defines the key for the matching process between order and product. To incorporate postprocessing, product agents anticipate their possibly reachable future states with first-principle models. The matching between order and product characteristics is then based on the predicted product future and the order specification. As the post-processing comes at a cost, logistics costs, administrative costs and transformation costs are also considered for constructing the virtual price. The presented system runs as online open-loop prototype at a steel plant of ArcelorMittal and shows promising results for the reallocation task.